On Pre-Proper Functions - Mahmood, Sabiha I (Al-Nahrain Journal of Science, 2011)
In this paper we introduce new type of functions called pre-proper functions as generalization of proper functions. Also, we study the characterizations and basic properties of pre-proper and pre-closed functions. Moreover we study the relation between the pre-proper functions and each of proper functions, pre-closed functions and closed functions respectively and we give an example when the converse may not be true.